Democrats on the Streets. Drivers of Student Protest Participation in Romania - Burean, Toma (PARTECIPAZIONE E CONFLITTO, 2019)
Since 2011, protests in post-communist Romania have changed their goals. Protesters claim to guard fundamental values of democracy such as the rule of law and fair representation and to rise against institutions crippled by corruption. In similar fashion to the 1989 revolution and the early 1990s protests, students have assumed an active role in these events. They took to the streets in Bucharest, Cluj, Ia?i and Timi?oara, the country’s four largest cities, and elsewhere. Over the same period, social media has proven essential for the gathering of information, for coordinating collective action and expressing the young protesters’ identity. Yet recent research (Badescu and Sum 2018) canvasses a gloomy picture of Romanian youth, said to have an eroded democratic profile. This situation is not unique. In Hungary, age and the display of authoritarian attitudes are inversely related, unlike in Poland (Fesnic 2015). Eastern Europeans might have finally rejected the remnants of the previous regime, yet the new generation is eager to embrace values that are not necessarily democratic. Value change trends bring out new interpretations to the way the transition to democracy unfolds in Eastern Europe. This paper addresses this contrast by discovering the combination of attitudes that drives youth to protest. With the help of a student survey conducted in 2017, it is shown that protest engagement is positively linked to the pro-democratic and diversity-embracing attitudes of students.